2013
DOI: 10.1038/nsmb.2570
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 4,5-bisphosphate clusters act as molecular beacons for vesicle recruitment

Abstract: Synaptic vesicle exocytosis is mediated by the vesicular Ca2+-sensor synaptotagmin-1. Synaptotagmin-1 interacts with the SNARE protein syntaxin-1A and with acidic phospholipids such as phosphatidylinositol 4,5-bisphosphate (PIP2). However, it is unclear how these interactions contribute to triggering membrane fusion. Using both PC12 cells from Rattus norvegicus and artificial supported bilayers we now show that synaptotagmin-1 interacts with the polybasic linker region of syntaxin-1A independent of Ca2+ via PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
313
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 263 publications
(341 citation statements)
references
References 57 publications
26
313
2
Order By: Relevance
“…Given the close proximity of the lysine-rich cluster and the CBR, these results are compatible with a parallel orientation model (Fig. 6F) in which these two motifs would interact with a vesicle representing the plasma membrane, leaving the bottom face free to interact in trans with another lipid vesicle (19,(47)(48)(49)(50)(51). How these two C2 domains act in tandem and in cooperation with other SNARE proteins to regulate vesicle fusion is still under debate and will need further exploration.…”
Section: Resultssupporting
confidence: 68%
“…Given the close proximity of the lysine-rich cluster and the CBR, these results are compatible with a parallel orientation model (Fig. 6F) in which these two motifs would interact with a vesicle representing the plasma membrane, leaving the bottom face free to interact in trans with another lipid vesicle (19,(47)(48)(49)(50)(51). How these two C2 domains act in tandem and in cooperation with other SNARE proteins to regulate vesicle fusion is still under debate and will need further exploration.…”
Section: Resultssupporting
confidence: 68%
“…EPR studies also yielded strong support for the direct bridging model for lnC 2 AB (24), and no oligomerization of lnC 2 AB under membrane bridging conditions was observed by EPR (24) or fluorescence spectroscopy (44). The study that proposed the oligomerization model using lnC 2 AB (29) did not account for the EPR data or the results that were already available for C 2 AB (20); relied on the cryo-EM images of a separate study (25); and supported the model with a series of indirect experiments, without providing direct evidence for the existence of proteinprotein interactions that help to bridge the membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it appears to be necessary for Ca 2ϩ sensor Syt1 to gain intimate access to the SNAREpin (32). In fact, it is shown that Syt1 has the capacity to bind the SNARE core and negatively charged lipids clustered in the immediate vicinity of the SNARE complex (38,54).…”
Section: Discussionmentioning
confidence: 99%